Attributes Influencing Strategic Alignment in the Service Sector: An Indonesian Banking Sector Case Study - Yuliansyah, Yuliansyah (International Journal of Business, Economics and Management, 2015)
Strategic alignment of manufacturing has been researched for more than four decades while research on service strategic alignment research is scarce. This paper is to explore attributes of strategic alignment in the service sector based on the manufacturing alignment literature modified for the service sector. Through a process of interviews of 14 senior managers in Indonesian banks I have identified new dimensions of service strategic alignment. A significant attribute to emerge which was most important in the context of Indonesian banking was standard operational procedures (SOPs), which ended up being the most important.